20 years of marine bioinvasions research: Achievements and challenges for the Southwestern Atlantic - Schwindt, Evangelina (2022)
The study of marine bioinvasions was not homogenously developed worldwide and it is unclear the amount of research effort currently applied across the Southwestern Atlantic (SWA) countries. Through a comprehensive literature review, in this work, we analyze trends, gaps and achievements in the marine bioinvasion research efforts made along the coastal-marine ecosystems of the SWA and over the last 20 years of development, and we identify current challenges to further strengthening regional and international policies and management decisions concerning coastal-marine invasive species. Our analysis showed an exponential growth in the research effort, mostly focused on ecological patterns of non-native species, while other categories of studies (e.g., processes, management, methodological and socio-ecological) received significantly less attention. We found a high prevalence of national studies, while regional and international collaborations were virtually nil. Although the three countries in the region have made important achievements regarding the study and management of marine bioinvasions, changing this unbalance in the research effort between national and international collaborations, and specifically the limited scientific collaborations across the SWA countries, should be a top priority to better deal with marine bioinvasions in a regional and global context.